Influence of solid loading on D-xylose production through dilute sulphuric acid hydrolysis of olive stones - M. Cuevas; M. Saleh; J. F. García-Martín; S. Sánchez (Grasas y Aceites, 2015)
The selective hydrolysis of hemicellulose from olive stones was attempted in order to achieve a maximum D-xylose yield. For this aim, batch hydrolysis was conducted under different operating conditions of temperature, acid concentration and solid loading. Firstly, distilled water, sulphuric acid and nitric acid were assessed as hydrolytic agents at different temperatures (200, 205, 210 and 220 °C) and at a fixed acid concentration (0.025 M). Sulphuric acid and 200 °C were selected for the subsequent dilute acid hydrolysis optimization based on the obtained D-xylose yields. The combined influence of solid loading (from 29.3 to 170.7 g olive stones into 300 mL acid solution) and sulphuric acid concentration (0.006–0.034 M) on the release of D-xylose was then estimated by response surface methodology. According to a statistical analysis, both parameters had significant interaction effects on D-xylose production. The results illustrated that the higher the solid loading, the higher the required acid concentration. The decrease in the solid/liquid ratio in the reactor had a positive effect on D-xylose extraction and on the amount of acid used. The optimum solid loading and sulphuric acid concentration were determined to be 50 g (solid/liquid ratio 1/6) and 0.016 M, respectively. Under these conditions, the predicted D-xylose yield (expressed as g of sugar per 100 g of dry matter fed) was 20.4 (87.2% of maximum attainable).